Patient-reported outcomes measured by BREAST-Q after implant-based breast reconstruction: A cross-sectional controlled study in Brazilian patients. (February 2017) - Aguiar, Isabella de Carvalho; Veiga, Daniela Francescato; Marques, Thaline Figueiredo; Novo, Neil Ferreira; Sabino Neto, Miguel; Ferreira, Lydia Masako
Abstract: Objective: The purpose of this study was to assess patient-reported outcomes of breast reconstruction with implants, using the BREAST-Q, in the late postoperative period. Materials and methods: A total of 114 women previously operated due to breast cancer, in the late postoperative period (range 6–24 months) were enrolled in this cross-sectional study, and were allocated to either the mastectomy group (MG, n = 57) or reconstruction group (RG, n = 57). Patients in MG and RG, respectively, completed the Brazilian versions of Mastectomy and Reconstruction Modules of the BREAST-Q. Results: The mean age of patients was 46.6 and 44.3 years in MG and RG, respectively. All patients underwent chemotherapy and 6% and 11% of patients underwent radiotherapy in MG and RG, respectively. Patients in the RG reported higher satisfaction with surgical outcome ( P < 0.0001). However, no significant between-group differences were found in physical and sexual well-being, or satisfaction with the plastic surgeon, medical team, and office staff. Conclusion: Breast reconstruction with implants increased patient satisfaction with the surgical outcome, but did not influence patients' physical and sexual well-being or their satisfaction with the treatment received. Highlights: Assessment of patient-reported outcomes in Brazil is not performed routinely. BREAST-Q outcomes from patients undergoing mastectomy alone or breast reconstruction. Unique controlled study that used BREAST-Q for this purpose, in Brazilian patients.